Proyecto de factibilidad para la implementación de una empresa productora y comercializadora de tintura de café embotellada en la ciudad de Loja - Castillo Chuquimarca, Katheryne Yadira (2018)
This research work refers to the "FEASIBILITY PROJECT FOR THE IMPLEMENTATION OF A PRODUCTION AND COMMERCIALIZING COMPANY OF BOTTLED COFFEE DYE IN THE CITY OF LOJA" that will serve as a guide to generate a new business project that provides society with a new product and innovative. Its main objective is to carry out a feasibility project for the implementation of a company, producer and marketer of tincture of bottled coffee in the city of Loja. To determine the feasibility of the project, the specific objectives were raised, which involve the elements of the investment project such as: market study, technical study, administrative study, financial study and financial evaluation. In the market study it was determined that there is an effective demand for the first year of 54,470 liters, therefore within the technical study the company in the city of Loja will develop its activities with an installed capacity of 87,600 liters per year and a capacity used of 18,720 liters for the 10 years of the project taking into account that the machinery will operate 75% of its capacity. In the Administrative Study it was determined that the company will have 4 hierarchical levels: Executive, Advisor, Assistant, and Operative, also requires hiring 6 people, creating work sources. The company will be incorporated under the legal form of Unipersonal Limited Liability Company, its corporate 6 name is "TINTURA COFFEE."; Its term will be 10 years. Within the analysis of the financial study, the investments in fixed assets, deferred and working capital required by the project were determined, establishing that $ 13,779.34 must be invested for the operation of the company in the first year; of this total, 64% is the contribution of own capital and the remaining 36% will obtain a credit in the Bank of the Ecuadorian Institute of Social Security with an annual interest rate of 10.21%. The total cost for the first year of production is of $ 92,286.66, with a production of 18,720 liters, the unit cost is of $ 4.93, to which is added the 18% of profit and the margin of distribution reaching a price adjusted sale of $ 5.85. According to the estimations made, the company will have a net profit of $ 9,983.04 for the first year of useful life and the cash flow shows that in this same period the company will have a net flow of $ 11,641.90. After having made the financial evaluation, with its respective indicators the project has a Net Present Value of 55,708.01 dollars, the Internal Rate of Return was 85.23% higher than the opportunity cost, the Benefit Cost Ratio shows that for each dollar invested, it generates $ 0.18 ctvs of profit, within the Capital Recovery Period, the capital invested is recovered in 1 year, 6 months, obtaining as a result positive indicators, which assure that this project can be carried out without greater difficulties. Finally, the sensitivity analysis shows that the project supports an increase in costs of up to 11.65% and a decrease in its revenues of up to 9.83%. Therefore, by carrying out the pertinent studies, it is concluded that it is feasible for its implementation and its execution is recommended since it envisages that profitability and economic benefits will be obtained as soon as the operational phase of the company begins.